The effect of local photodynamic therapy with 5-aminolevulinic acid for the treatment of cervical low-grade squamous intraepithelial lesions with high-risk HPV infection: A retrospective study - Gu, Liying; Cheng, Mengxing; Hong, Zubei; Di, Wen; Qiu, Lihua (Photodiagnosis and photodynamic therapy, 2021)
•5-aminolevulinic acid photodynamic therapy is a highly effective and non-invasive therapeutic procedure for cervical LSIL patients in all age.•5-aminolevulinic acid photodynamic therapy can also remove high risk HPV infection rapidly and maintain the effect for a long time.•5-aminolevulinic acid photodynamic therapy may have wide application prospect in cervical LSIL with different genotype high risk HPV infection.•For patients over 50 years old, close follow-up monitoring after the therapy should be applied. High-risk HPV infection is the main cause of cervical cancer and pre-cancerous lesions. The current principle of clinical management of cervical low-grade squamous intraepithelial lesion is observation for 2 years. Progression to high-grade squamous intraepithelial lesion warrants intervention. Primary treatment option is surgical excision which may have a negative impact on fertility. Topical photodynamic therapy is a non-invasive and targeted therapy. We investigated the clinical efficacy of this therapy for cervical low-grade squamous intraepithelial lesion with high-risk HPV infection. A retrospective study consisting of 258 female patients aged 21–69 years with a histologically confirmed cervical low-grade squamous intraepithelial lesion with high-risk HPV infection was carried out. Subjects were treated with three sessions of 20 % 5-aminolevulinic acid photodynamic therapy at intervals of 7–14 days. Three months after treatment, the effect was evaluated through HPV typing, Thinprep cytology and colposcopy directed biopsy. Six months after treatment, the photodynamic therapy effect was evaluated by HPV genotyping and Thinprep cytology first, the pathological examination would be performed at the 6-month follow-up point if the cytological results indicated the risk of high-grade squamous intraepithelial lesions. Three months after treatment, among 258 low-grade squamous intraepithelial lesion with high-risk HPV infection patients, total baseline HPV remission rates was 64.34 % (166/258). The remission rate of HPV16/18 group was not statistically significant compared to the HPV non-16/18 group (73.13 % vs 61.26 %, p = 0.081).The remission rates of the <50 age group was significantly higher than the >50 age group (67.28 %vs46.34 %, p = 0.001). The total lesion regression rate wa treatment, among 258 low-grade squamous intraepithelial lesion with high-risk HPV infection patients, total baseline HPV remission rates was 64.34 % (166/258). The remission rate of HPV16/18 group was not statistically significant compared to the HPV non-16/18 group (73.13 % vs 61.26 %, p = 0.081).The remission rates of the <50 age group was significantly higher than the >50 age group (67.28 %vs46.34 %, p = 0.001). The total lesion regression rate was 84.88 % (219/258). 12.8 % (33/258) of patients did not progress. Only 2.33 % (6/258) patients progressed to high-grade squamous intraepithelial lesion and accepted loop electrosurgical excision procedure. The patients >50 age group had significant higher progression rate than the patients ＜50 age group (p＜0.05). Six months after treatment, except for 6 patients who progressed to high-grade squamous intraepithelial lesion and underwent surgical treatment, the total baseline HPV remission rates was up to 82.54 % (208/252). 5-aminolevulinic acid photodynamic therapy was highly effective and did not appear to create cervical damage.. It might be an ideal treatment for cervical low-grade squamous intraepithelial lesion with high-risk HPV infection, but this requires additional clinical trials.